Implementation Implementation of the Applicability of the Death Penalty in Indonesia Through a Review of Pancasila-Based Islamic Law - Yenny Febrianty; Mustika Mega Wijaya; Asmak Ul Hosna; Farahdinny Siswajanthy; Isep H Insan (Green Publisher Indonesia, 2023)
Islamic law provides a sense of justice including in the threat of sanctions for crimes committed, Islamic law places punishments commensurate with the crimes so as to create a sense of deterrent effect for perpetrators and society. Including the death penalty. This paper raises two issues that will be discussed, namely: How is the contribution of Islamic law in determining death penalty laws in Indonesia and how is the legal politics of death penalty provisions applicable in Indonesia based on Pancasila? The Normative Juridical Approach is used as the writing technique of this research. This study aims to conduct legal research using library materials, secondary data, and original data as additional data. From the discussion of this paper, it can be concluded that the existence of Islamic law, especially regarding the death penalty in Indonesia, has a very strong contribution to punishment in general in Indonesia. Because Islamic law, especially in the case of the death penalty, determines the appropriate punishment for the perpetrator, and because of the legal politics of the death penalty, which is understood as the direction of legal policy regarding the death penalty, this includes the state. policies on how the death penalty is carried out and how it should be carried out.